Визначення кінематичних параметрів прикочувальних роликів гранулятора з плоскою матрицею - Комар, Артем Станіславович; Комар, Артем Станиславович; Komar, Artem (My University, 2021)
UK: Процеси гранулювання матеріалів є масовими технологічними процесами, які в даний час знайшли застосування в сільському господарстві. Якщо комплексні теоретичні дослідження конструкції грануляторів з кільцевою матрицею вивчалися досить докладно, то дослідження кінематики руху робочих органів грануляторів з плоскою матрицею практично не проводилися. Кінематика руху робочих органів визначає характер їх руху і швидкісні параметри, а також витрати енергії на роботу агрегату. У зв'язку з цим для формування гранул з пташиного посліду в грануля-торах з плоскою матрицею в даній статті досліджено рух прикочувального ролика по нерухомо закріпленій матриці і обертанням його навколо своєї осі. Розглянуто сили, що діють на циліндричний прикочувальний ролик при його роботі. Визначено кінематичні параметри та встановлений їх взаємозв'язок з конструктивними параметрами прикочувального ролика. Отримано аналітичні рівняння визначення нейтрального перетину (найбільш характерного) прикочувального ролика гранулятора, моменту приведення в рух прикочувального ролика та потужності необхідної для перекочування декількох прикочувальних роликів. EN: The processes of granulating materials are massive technological processes that are currently widely used in almost all industries, in particular in agriculture. This is due to the advantages of granules in comparison with powdered, pasty and liquid forms of substances. Granules have good mobility, they do not stick to the hopper surface, do not cake during storage, do not generate dust during transportation and packaging. The use of granular intermediates allows you to intensify the technological process, improves the sanitary conditions of work. For the introduction of automatic dosing and filling systems, it is necessary to obtain a product in granular form. The use of such progressive types of transportation of materials as pneumatic and vibration transport is often possible only in the presence of granular non-dusting products. The die press granulator has taken the lead over the competition. If complex theoretical studies of the design of granulators with an annular matrix were studied in sufficient detail, then studies of the kinematics of the movement of the working bodies of granulators with a flat matrix were practically not carried out. A detailed analysis of the kinematic diagram of the installation allows a rational approach to the design process of new equipment, and the kinematics of the movement of the working bodies determines the nature of their movement and speed parameters, as well as the energy consumption for the operation of the unit. In this regard, for the formation of pellets from bird droppings in granulators with a flat matrix, movement of the press roller on a fixed matrix and rotation around its axis are discusses in this article. Analytical studies of the interaction of the active working organs of the granulator with a flat matrix have been are carried out. The forces acting on a cylindrical press roller during its operation are considered. The kinematic parameters are determined and their relationship with the design parameters of the press roller is established. Analytical equations are obtained: determination of the neutral section (the most characteristic), the moment of driving the granulator press roller and the power required for rolling several press rollers. RU: Процессы гранулирования материалов являются массовыми технологическими процессами, которые в настоящее время нашли применение в сельском хозяйстве. Если комплексные теоретические исследования конструкции грануляторов с кольцевой матрицей изучались достаточно подробно, то исследования кинематики движения рабочих органов грануляторов с плоской матрицей практически не проводились. Кинематика движения рабочих органов определяет характер их движения и скоростные параметры, а также затраты энергии на работу агрегата. В связи с этим для формирования гранул из птичьего помета в грануляторах с плоской матрицей в данной статье исследовано движение прикатывающего ролика по неподвижно закрепленной матрицы и вращением его вокруг своей оси. Рассмотрены силы, действующие на цилиндрический прикатывающий ролик при его работе. Определены кинематические параметры и установлена их взаимосвязь с конструктивными параметрами прикатывающего ролика. Получены аналитические уравнения для определения нейтрального сечения (наиболее характерного) прикатывающего ролика гранулятора, момента приведения в движение прикатывающего ролика и мощности необходимой для перекатывания нескольких прикатывающих роликов.
Determination of the press rollers kinematic parameters granulator with flat matrix
Определение кинематических параметров прикатывающих роликов гранулятора с плоской матрицей
Keywords: гранулятор; прикочувальний ролик; плоска матриця; кінематичні параметри; прикладені сили; пташиний послід; granulator; press roller; flat matrix; kinematic parameters; applied forces; bird droppings; гранулятор; прикатывающий ролик; плоская матрица; кинематические параметры; приложенные силы; птичий помет